2022
DOI: 10.1038/s41380-022-01841-y
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota regulates chronic ethanol exposure-induced depressive-like behavior through hippocampal NLRP3-mediated neuroinflammation

Abstract: Chronic ethanol exposure (CEE), which can lead to neuroinflammation, is an increasing risk factor for depression disorder, but the underlying mechanism is not clear. Recent observations have revealed the associations among psychiatric disorders, ethanol exposure and alterations of the gut microbiota. Here, we found that CEE induced depressive-like behavior, which could be alleviated by probiotics and transferred from donor to recipient mice by fecal microbiota transplantation (FMT). Neuroinflammation and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Similar mechanisms were indicated by experiments in mice with lung cancer 32 . Alcohol exposure regulates gut microbiota and mediates anxiety and depression through NLRP3‐mediated neuroinflammation 33,34 …”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Similar mechanisms were indicated by experiments in mice with lung cancer 32 . Alcohol exposure regulates gut microbiota and mediates anxiety and depression through NLRP3‐mediated neuroinflammation 33,34 …”
Section: Discussionsupporting
confidence: 55%
“…32 Alcohol exposure regulates gut microbiota and mediates anxiety and depression through NLRP3-mediated neuroinflammation. 33,34 This analysis not only illuminates the potential mechanisms affecting mental well-being but also provides valuable insights for clinical practice. Depression and anxiety significantly affect patient prognosis, and there is a concerted effort to alleviate such distress.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the molecular basis of memory formation has also been shown to involve innate immune sensing of endogenous genomic damage induced by neural activity 50 . In the context of disease, pathogen sensors and inflammatory cytokines have been implicated in a variety of neurologic and behavioral outcomes [51][52][53][54][55] , including sickness behavior [56][57][58] , and inflammation generally is known to drive pathologic processes in neurons including aberrant synaptic pruning 6,59,60 , excitotoxicity 23,61,62 , and epileptogenesis 63,64 . Our results describe a nexus of neuroimmune signaling in which activation of RIPK3 dampens neuronal excitability, which in turn promotes survival in the presence of excitotoxic levels of glutamate during CNS viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of the in ammasome in psychiatric disorders such as MDD is less well understood. Numerous preclinical studies have reported that activation of the NLRP3 in ammasome is associated with depressive-like behaviors in rodents [19][20][21][22][23][24] . Nevertheless, there is a paucity of in ammasome-focused research in clinical populations with only a handful of small (n < 50) human studies published to date.…”
Section: Introductionmentioning
confidence: 99%